The value of local language in the management of HIV/AIDS in the world of work - Adams, Freda Johanna (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. HIV/AIDS Management))--University of Stellenbosch, 2009.